Castle Court, Ganges - A book of the Cevennes - Sabine Baring-Gould (Wikimedia Commons, 1907)
Carte postale ancienne issue de Wikimedia Commons. Titre: Castle Court, Ganges - A book of the Cevennes. Image from scanned version of "A Book of The Cevennes" by Sabine Baring-Gould, from https://archive.org/details/bookofcevennes00bariuoft, published in 1907 and in the Public Domain. Image cropped. Slight adjustments to exposure and slight sharpening. Sepia tone removed
Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; Château